HUBUNGAN LINGKAR PERUT DENGAN KEJADIAN PREDIABETES DI POSBINDU PTM UPTD PUSKESMAS SIPEA PEA - K. Simamora, Yenni Clarisza; Nasution, Yulia Afrina (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract : Health in this world is now affected by obesity. Excessive fat accumulation resulting from a long-term mismatch between calorie intake and energy expenditure is known as obesity. Obesity is considered to exist if the body mass index (BMI) is more than 30 kg/m2. Increased visceral fat is linked to metabolic disorders, which can worsen insulin sensitivity and glucose tolerance, thereby increasing blood sugar levels. Prediabetes, which will eventually lead to diabetes mellitus, is a risk factor for this disease. Impaired glucose tolerance or impaired fasting blood sugar levels are symptoms of prediabetes. This research aims to understand the relationship between abdominal circumference and the prevalence of prediabetes in the working area of the UPTD Sipea Puskesmas kacang. The research method used is analytical descriptive research, with a cross sectional study research design, where the researcher only studies the subject once at a certain time. This research was conducted at the PTM Posbindu UPTD Sipea Pea in West Sorkam District, Central Tapanuli Regency, North Sumatra. Based on the results of the Spearman test, 50 respondents met the prediabetes criteria, with 11 respondents having a percentage of 22% and 39 respondents having a percentage of 78%. The p-value = 0.041. There is a significant relationship between abdominal circumference and the incidence of prediabetes at UPTD Sipea Health Center